Zandi and the Wonderful Pillow - Chukwuka, J.I.N. (African Universities Press, 1977)
Customarily, any child born with a humpback in this village is thrown into the Evil Forest and left to die. Zandi tries to escape this customary ordeal. Did he succeed? What were the results?
Keywords: Juvenile Fiction / Realistic / tradition